How to improve firm performance through employee diversity and organisational culture - Triguero-Sánchez, Rafael (2018)
Purpose – Our study examines the influence that employee diversity has on human resource management (HRM) practices and organisational performance, considering the moderating role of organisational culture, in particular, cultural dimensions such as individualism–collectivism and hierarchical distance. Design/methodology/approach – Through an empirical investigation of 102 Spanish firms using partial least squares-structural equation modelling (PLS-SEM), we evaluated our hypotheses. Findings – Our results show a positive correlation between employee diversity and HRM practices where such practices encourage employee commitment rather than control. Thus, we identified a non-linear relationship between HRM practices and organisational performance.Originality/value – The study considers the role played by environmental and contextual factors, such as organisational culture. The configuring of HR practices may help to reduce the possible costs derived from a diverse staff and improve their skills in favour of better organisational performance.